KIT mutation and loss of 14q may be sufficient for the development of clinically symptomatic very low-risk GIST - Klinke, Olaf; Mizani, Tuba; Baldwin, Gouri; Bancel, Brigitte; Devouassoux-Shisheboran, Mojgan; Scoazec, Jean-Yves; Bringuier, Pierre-Paul; Feederle, Regina; Jauch, Anna; Hinderhofer, Katrin; Taniere, Philippe; Delecluse, Henri-Jacques (PLOS ONE, 2015)
The aim of this study was to determine the minimal set of genetic alterations required for the development of a very low risk clinically symptomatic gastro-intestinal stromal tumour within the stomach wall. We studied the genome of a very low-risk gastric gastro-intestinal stromal tumour by whole-genome sequencing, comparative genomic hybridisation and methylation profiling.